Penyuluhan Dismenore serta Upaya Penanganan kepada Remaja Putri Dukuh Dukuhan Desa Sambirejo - Rahmawati, Elsa (Universitas Sebelas Maret, 2023)
Menstrual pain is also known as dysmenorrhea, which can be divided into primary and secondary types. Most adolescents with menstrual pain experience primary dysmenorrhea, without a pathological cause, in contrast to secondary dysmenorrhea which can be caused by endometriosis, myoma or infection. About 30% of young women (that is, women aged 12-25) report experiencing severe menstrual pain, which is often associated with symptoms such as back pain, nausea, fatigue, headache and diarrhea. The method used is discussion and counseling with the theme of getting to know more about dysmenorrhea with an emphasis on handling efforts when dysmenorrhea occurs. Socialization is carried out by providing an explanation of the occurrence of dysmenorrhea. In addition, participants were also explained in an easy and interesting way about the types of dysmenorrhea, the health impacts they cause and the factors that can increase the occurrence of dysmenorrhea. The explanation was also accompanied by display of pictures, leaflets and discussions so that the participants could understand more about dysmenorrhea and how to deal with it. The young women of Dukuh Dukuhan, Sambirejo Village, received enlightenment and clear explanations about dysmenorrhea and gain knowledge about a clean and healthy lifestyle (PHBS) and good stress management.